Retrospective study of eligibility for orthognathic surgery using the Index of Orthognathic Functional Treatment Need (IOFTN). Issue 5 (June 2018) - Fowler, P.; King, T.; Lee, M.; Erasmus, J.
Abstract: To assess the functional needs of orthognathic patients who had been accepted for treatment by Christchurch Hospital, New Zealand, we made a retrospective assessment of 80 consecutive patients using the Index of Orthognathic Functional Treatment Need (IOFTN). Eligibility was based on the Severity and Outcome Index (SOI) score of ≤3 derived from seven lateral cephalometric measurements (three skeletal, three dental, and one soft tissue), which made allowances for asymmetrical or reported important functional issues. The IOFTN grades 4 or 5 indicated "great" or "very great" need for treatment, and we also used a self-reported oral health-related quality of life (QoL) questionnaire (OHIP-14). Sixty-eight patients were considered eligible using the SOI, and 71 when the IOFTN was used. Eight who were eligible using the SOI would not have been eligible using the IOFTN while 11 who were not considered eligible using the SOI scored ≥4 using the IOFTN. However, when it was compared with the SOI, the IOFTN tended to underscore those patients who were Class III/skeletal 3 with reverse overjets of <3 mm and with no reported functional difficulties, while it tended to overscore Class II/skeletal 2 patients with overjets ≥6 mm. We found no association found between the OHIP-14 and the SOI or the IOFTN. Further investigations are required to clarify functional difficulties that are applicable to the IOFTN grading, and to find out the most appropriate self-reported, oral-health-related QoL measure(s) to complement the use of the IOFTN.